Changes in the Surface Water Nitrogen Content in the Upper Hun River Basin, Northeast China. (31st July 2022) - Jin, Wenkai; Ma, Jian; Chen, Xin; Yan, Guohui
Abstract : Human activities have considerably increased nitrogen intake into waterways, resulting in the deterioration of water quality. The state of surface water requires special consideration in light of the water crisis caused by nitrogen pollution. In this study, the natural abundance of the nitrogen stable isotope ( δ 15 N) is measured and sampled in sediments and compared with the total dissolved nitrogen (DN) in four main Chinese tributaries of Hun River upper reach, including the Dasuhe, Beisanjia, Beikouqian, and Nanzamu tributaries. Results show that for the Dasuhe and Nankouqian tributaries, the δ 15 N values of sediment samples in 2016 are all significantly higher than previous values in 2011. In the Dasuhe tributary, this change is attributed to the promotion of organic agricultural production under which chemical fertilizers are replaced by organic fertilizers. For the δ 15 N values of the sediment in the Nankouqian tributary, the construction of the municipal sewer system and wastewater treatment facilities are the causes of this rising trend. The δ 15 N values of nitrate released by facilities could be raised by microbial denitrification that is employed in the tertiary treatment process. Most of the δ 15 N values of the sediments are distributed between soil and manure, indicating that nitrogen in the river water mainly comes from agriculture. All the surveyed tributaries except Dasuhe show a significant increase in DN. In addition, a significant positive correlation between the change ratio of the farmland area and DN in river water is observed, suggesting that the increase in nitrogen in river water from 2011 to 2016 is due to agriculture. Based on the abovementioned data, this study provides a basis for local governments to formulate management measures.